Upaya Meningkatkan Kemampuan Problem Solving Melalui Metode Inquiry - Soleman Talib; Safri Tinamba (Peneliti.net, 2019)
This study aims to determine the improvement of problem solving skills of class X students on material derived functions through themethod Inquiry. This type of research is Classroom Action Research (CAR). The subjects in this study were class X students of SMA Negeri 9 Kota Tidore Kepulauan, totaling 31 students. Research carried out with 1-2 cycles. Data retrieval in this study was carried out using a problem solving ability test and an observation sheet of the teacher's ability to manage learning based onmethods inquiry and observing student activities in learning based onmethods inquiry. Based on the results of data analysis in the field, it is necessary to improve the quality of learning by offering a variety of methods. One of the methods used is themethod which is Inquiry very effective in mathematics learning, especially learning materials that require the ability to orient on problems, formulate problems, formulate hypotheses, collect data, test hypothesis, and formulating conclusions because it can improve problem-solving abilities.